STUDI PERSEPSI MASYARAKAT TERHADAP KEBERADAAN PELABUHAN PERIKANAN PANTAI TASIKAGUNG REMBANG - Zulfa, Nely; Mulyawati, Isti (Environmental Science Program, Ivet University, 2020)
Fishery port is a fisheries industry development area which is an economic development embryo in an area. The existence of a fishing port is also one of the efforts in the context of accelerating the progress of the coastal region, by optimizing coastal resources, through improving facilities and infrastructure in the fisheries sector. Waste material in the coastal area is mostly discharged into the sea. Routine activities that occur in fishing ports have the potential to become sources of pollution. That is because the waste originating from fishery activities has the potential to cause pollution to the aquatic environment including waste which is one of the main ingredients contained in domestic waste disposal. Organic waste is waste that in the process of decomposition requires oxygen. The results of sea water sampling in the coastal fishing port area indicate the occurrence of sea water pollution. So it is necessary to study how the community's perspective with the presence of coastal fishing ports. The method used is in-depth interviews with actors in coastal fishing ports and the local community. Perception of the assessment of the existence of the Tasikagung coastal fishing port can include water quality, economic, social and institutional. The total number of respondents gave responses to the existence of the Tasikagung coastal fishing port agree (85%), enough (10%), strongly agree (5%) and strongly disagree, disagree (0%) means that the Tasikagung community is very positive about the existence of the Port Tasikagung Beach Fisheries. The existence of the Tasikagung coastal fishing port is very influential on the economic sector of the people of Rembang and surrounding areas